Short- and Long-Term Results of Transcatheter Embolization for Massive Arterial Hemorrhage from Gastroduodenal Ulcers Not Controlled by Endoscopic Hemostasis. (2009) - Loffroy, Romaric; Guiu, Boris; Mezzetta, Lise; Minello, Anne; Michiels, Christophe; Jouve, Jean-Louis; Cheynel, Nicolas; Rat, Patrick; Cercueil, Jean-Pierre; Krausé, Denis
Abstract : BACKGROUND AND AIM: Severe bleeding from gastrointestinal ulcers is a life-threatening event that is difficult to manage when endoscopic treatment fails. Transcatheter embolization has been suggested as an alternative treatment in this situation. The present study reports on the efficacy and long-term outcomes of transcatheter embolization after failed endoscopic treatments were assessed in high-operative-risk patients. METHODS: A retrospective review of 60 consecutive emergency embolization procedures in hemodynamically unstable patients (41 men, 19 women; mean [±SD] age 69.4±15 years) was conducted. Patients were referred for selective angiography between 1999 and 2008 after failed endoscopic treatment of massive bleeding from gastrointestinal ulcers. Mean follow-up was 22 months. RESULTS: Embolization was feasible and successful in 57 patients. Sandwich coiling of the gastroduodenal artery was used in 34 patients, and superselective occlusion of the terminal feeding artery (with glue, coils or gelatin particles) was used in 23 patients. Early rebleeding occurred in 16 patients and was managed with endoscopy (n=8), reembolization (n=3) or surgery (n=5). No major embolization-related complications occurred. Sixteen patients died within 30 days after embolization (including three who died from rebleeding) and 11 died thereafter. No late bleeding recurrences were reported. CONCLUSIONS: Selective angiographic embolization is safe and effective for controlling life-threatening bleeding from gastroduodenal ulcers. The procedure usually obviates the need for emergency surgery in these high-risk patients. Survival depends chiefly on underlying conditions.